Auroral ion acoustic wave enhancement observed with a radar interferometer system - Schlatter, Nicola M.; Belyey, Vasyl; Gustavsson, Björn Johan; Ivchenko, Nickolay; Whiter, Daniel; Dahlgren, Hanna; Tuttle, Sam; Grydeland, Tom (Annales Geophysicae, 2015)
Published version. Source at http://doi.org/10.5194/angeo-33-837-2015 . Measurements of naturally enhanced ion acoustic line (NEIAL) echoes obtained with a five-antenna interferometric imaging radar system are presented. The observations were conducted with the European Incoherent SCATter (EISCAT) radar on Svalbard and the EISCAT Aperture Synthesis Imaging receivers (EASI) installed at the radar site. Four baselines of the interferometer are used in the analysis. Based on the coherence estimates derived from the measurements, we show that the enhanced backscattering region is of limited extent in the plane perpendicular to the geomagnetic field. Previously it has been argued that the enhanced backscatter region is limited in size; however, here the first unambiguous observations are presented. The size of the enhanced backscatter region is determined to be less than 900 × 500 m, and at times less than 160 m in the direction of the longest antenna separation, assuming the scattering region to have a Gaussian scattering cross section in the plane perpendicular to the geomagnetic field. Using aperture synthesis imaging methods volumetric images of the NEIAL echo are obtained showing the enhanced backscattering region to be aligned with the geomagnetic field. Although optical auroral emissions are observed outside the radar look direction, our observations are consistent with the NEIAL echo occurring on field lines with particle precipitation.